Whole-genome resequencing reveals genetic diversity, differentiation, and selection signatures of yak breeds/populations in Qinghai, China - Li, Guangzhen; Luo, Jing; Wang, Fuwen; Xu, Donghui; Ahmed, Zulfiqar; Chen, Shengmei; Li, Ruizhe; Ma, Zhijie (Frontiers in Genetics, 2023)
Geographically, the Qinghai Province of China located in the northeast region of the Qinghai-Tibetan Plateau (QTP). It carries abundant yak genetic resources. Previous investigations of archaeological records, mitochondrial DNA, and Y chromosome markers suggested that the Qinghai region was served as one of the yak’s origin or/and domestication sites. In the present study, we examined the genomic diversity, differentiation, and selection signature of 113 Qinghai yaks (including 42 new Qinghai yaks and 71 corresponding publicly-available individuals) from nine yak breeds/populations (wild, Datong, Huanhu, Xueduo, Yushu, Qilian, Geermu, Tongde and Huzhu) through high-depth whole-genome sequencing datas. It is observed that the Huzhu white yak population has the highest genomic diversity (nucleotide diversity, inbreeding coefficient, linkage disequilibrium decay and runs of homozygosity). The population genetic structure analysis shows that Qinghai yak has two lineages with two origins and nine yak breeds/populations could be clustered into three distinct groups (wild yak, Geermu yak population, and other seven domestic yak breeds/populations). The estimates of FST values showed moderate genetic differentiation between wild yak, Geermu yak and the other Qinghai yak breeds/populations. The positive selection signals were predominantly detected in candidate genes associated with disease resistance (CDK2AP2, PLEC and CYB5B), stress (NFAT5, HSF1 and SLC25A48), melanogenesis (MCAM, RNF26 and BOP1), vision (C1QTNF5, MFRP and TAX1BP3), milk quality (OPLAH, GRINA and PARP10), neurodevelopment (SUSD4, INSYN1 and PPP1CA) and meat quality (ZRANB1) using integrated PI, CLR, and FST methods. These findings offered new insights into the genetic mechanisms underlying the target traits in yak and provided important information to understand genomic characterization of yak breeds/populations in Qinghai.